Lung cancer detection using SVM algorithm / Nur Qamarina Ainaa Zulkifli - Zulkifli, Nur Qamarina Ainaa (2024)
Lung cancer remains a significant global health challenge, with its prevalence escalating and posing a considerable threat to human life. Early detection plays a pivotal role in the effectiveness of treatment and patient prognosis. Lung tumors can be broadly categorized as either benign or malignant. It's important for individuals with lung nodules or suspected lung cancer to consult with healthcare professionals who can provide a thorough evaluation, accurate diagnosis, and appropriate treatment recommendations based on the specific circumstances of the case. This study has proposed a lung cancer detection model using support vector machine and a prototype was developed to detect whether it is cancerous or normal lung. The proposed model has achieved an accuracy percentage of lung cancer with 95.24%. The significance of this project is this prototype will give benefits to tall the medical officers in the hospital as they can check whether the patient has lung cancer or not.